Respiratory syncytial virus prefusogenic fusion (F) protein nanoparticle vaccine: Structure, antigenic profile, immunogenicity, and protection. Issue 41 (24th September 2019) - Patel, Nita; Massare, Mike J.; Tian, Jing-Hui; Guebre-Xabier, Mimi; Lu, Hanxin; Zhou, Haixia; Maynard, Ernest; Scott, Daniel; Ellingsworth, Larry; Glenn, Gregory; Smith, Gale
Abstract: Respiratory syncytial virus (RSV) is a major cause of severe respiratory disease in the very young, elderly, and immunocompromised for which there is no vaccine. The surface exposed RSV fusion (F) glycoprotein is required for membrane fusion and infection and is a desirable vaccine candidate. RSV F glycoprotein structure is dynamic and undergoes significant rearrangements during virus assembly, fusion, and infection. We have previously described an RSV fusion-inactive prefusogenic F with a mutation of one of two furin cleavage sites resulting in the p27 region on the N-terminus of F1 with a truncated fusion peptide covalently linked to F2. A processing intermediate RSV prefusogenic F has been reported in infected cells, purified F, budded virus, and elicited a strong immune response against p27 in RSV infected young children. In this report, we demonstrate that prefusogenic F, when expressed on the cell surface of Sf9 insect and human 293T cells, binds monoclonal antibodies (mAbs) that target prefusion-specific antigenic sites Ø and VIII, and mAbs targeting epitopes common to pre- and postfusion F sites II and IV. Purified prefusogenic F bound prefusion F specific mAbs to antigenic sites Ø and VIII and mAbs targeting pre- and postfusion sites II, IV, and p27. Mice immunized with prefusogenic F antigen produced significantly higher levels of anti-F IgG and RSV neutralizing antibodies than prefusion or postfusion F antigens and induced antibodies competitive with mAbs to sites Ø, VIII, II, and IV. RSV prefusogenic F neutralization antibody responses were enhanced with aluminum phosphate adjuvant and significantly higher than prefusion F. Prefusogenic F vaccine protected cotton rats against upper and lower respiratory tract infection by RSV/A. For the first time, we present the structure, antigenic profile, immunogenicity, and protective efficacy of RSV prefusogenic F nanoparticle vaccine.